Pediatric Acute Promyelocytic Leukemia: A Rare Case Report - Verma, Renuka; Rawat, Aakanksha; Kalra, Rajnish; Gupta, Monika; Ahlawat, Anjali; Rathee, Pooja (Annals of Pathology and Laboratory Medicine, 2023)
Acute Promyelocytic leukemia (APML) belongs to French American British (FAB) classification M3 subtype of acute myeloid leukemia & is characterized by t(15;17) and resultant PML-RARA fusion gene. APML accounts for 5-10 % in pediatric age group. Patients usually present with bleeding manifestations, weakness and increased propensity for disseminated intravascular coagulation. Extramedullary involvement is rare. It is a hematologic disease presenting as medical emergency and can be diagnosed with certainty by morphological examination of peripheral blood film & bone marrow aspirate to allow initiation of targeted therapy in order to reduce mortality. Patients with APML receive combination of all-trans retinoic acid (ATRA) & arsenic trioxide to induce terminal differentiation of blasts. We present a case of APML in a four years old child presented in the department of clinical hematology with pallor, lymphadenopathy and hepatosplenomegaly.